30. HIỆU QUẢ ĐIỀU TRỊ CỦA VIÊN NANG “HẠ MỠ NK” TRÊN MỘT SỐ CHỈ SỐ XƠ VỮA ĐỘNG MẠCH (Tạp chí Y học Cộng đồng, 2025)
Objectives: Evaluate the effect of improving AI, CRI, AIP and CAVI indexes of “Ha mo NK” capsules on atherosclerosis patients. Compare before and after treatmentSubject and methods: A randomized, controlled clinical trial with pre- and post-treatment comparisons conducted on 60 patients diagnosed with atherosclerosis. The patients were divided into two groups: the study group received “Ha mo NK” capsules (525 mg), 6 capsules/day, taken in two divided doses at 8:00 AM and 15:00 PM. The control group received Atorvastatin 10 mg, 1 capsules/day, taken at 8:00 PM. The treatment duration was 60 days.Results: “Ha mo NK” capsules were effective in reducing AI index by 26.04%; CRI index by 21.33%; AIP index by 37.93%; CAVI index by 3.13% with statistical significance with p < 0.001 equivalent to the Atorvastatin group: reducing AI index by 26.03%; CRI index by 20.95%; AIP index by 46.15%; 3.91% CAVI index with p < 0.001.Conclusions: “Ha mo NK” capsule has anti-atherosclerosis effects through AI, CRI, CRI and CAVI indexes equivalent to the Atorvasatin group.
Keywords: Xơ vữa động mạch; viên nang “Hạ mỡ NK